Pelindungan Hukum Hak Cipta Terhadap Reini Wirahadikusumah Sebagai Orang yang Menjadi Objek dalam Karya Cipta Potret yang Diunggah Tanpa Izin Sebagai Aset Digital Non-Fungible Token (NFT) - Gibson Batara Siahaan; Laina Rafianti; Mustofa Haffas (CV. Publikasi Indonesia, 2023)
Currenct technological developments support humans to be able to carry out economic activities without regional boundaries problems. One of the impacts is the Non-Fungible Token (NFT) technology that supports security in investement activites of copyrighted works that are converted into digital assets on digital platforms. However, the platform is also used by the irresponsible parties as a medium for copyright infringement, such as in the case of unauthorized sale of Reini Wirahadikusumah’s potrait as Chancellor of ITB on the OpenSea platform. This study aims to understand the legal protection related to the rights of Reini Wirahadikusumah as the person in the potret work and the appropriate legal action taken by Reini Wirahadikusumah for the illegal sale of the potrait work.